Cryopreservation of Echinococcus granulosus Protoscoleces - Alireza BADIRZADEH; Saber RAEGHI; Vahid FALLAH-OMRANI; Soheila ROUHANI (Tehran University of Medical Sciences, 2020)
Background: The main objective of the current study was to investigate on the cryopreservation of protoscoleces of Echinococcus granulosus, a causative agent of cystic hydatidosis in man. Methods:  This study was conducted on isolated protoscoleces from hydatid cysts infected livers collected from slaughterhouse of Tehran, Iran in 2016. Viability of protoscoleces was evaluated by dye test. Cryopreservation of isolated protoscoleces in the presence of Dimethylsulfoxide (DMSO) and glycerol using a three-step cooling protocol involving an initial period at -20 °C, -80 °C and liquid nitrogen was performed. Results: The mean viability rate of 10% DMSO and 15% glycerol were 9% and 8% respectively. The protoscoleces of Echinococcus granulosus have been successfully thawed and recovered after 6 months storage in liquid nitrogen. Conclusion: Cryopreservation method needs to be improved for each species of helminthes and can be useful for other immunological and laboratorial studies.